THE GROWTH PATTERNS OF CARCASS TISSUES WITHIN WHOLESALE CUTS IN FATTENING STEER - Priyanto, R.; Johnson, E.R.; Taylor, D.G. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
An investigation was conducted on beef carcasses, aimed at identifying the growth patterns of wholesalecuts and their tissues in steer during fattening phase. This study involved 69 grass-fed steers with a liveweightrange of 300 to 600 kg. They had entered, or were progressing along, their fat deposition phase. Anallometric model (Huxley, 1932) was used to study the growth patterns of carcass tissues within wholesalecuts. In general, The growths of muscle and fat within wholesale cuts followed similar patterns. Somedifferences in growth patterns between muscle and fat were identified on the dorsal region. The growth impetusfor fat moved from the thoracic backwards to the lumbar region which was the reverse of the growth impetus formuscle. Differential growth patterns occurred between intermuscular (IM) fat and subcutaneous (SC) fat. WithIM fat, its growth movement was similar to that of total fat where there was a concentration of growth in thelumbar area and thin flank as side weight increased. With SC fat, there were growth movements from the ventralregion to the dorsal region of the carcass. Bone growth within wholesale cuts showed a less clear pattern.